A High-Quality Genome Assembly of Sorghum dochna - Chen, Yu; Zhang, Yongbai; Wang, Hongjie; Sun, Juan; Ma, Lichao; Miao, Fuhong; Zhang, Zixin; Cheng, Yang; Huang, Jianwei; Yang, Guofeng; Wang, Zengyu (Frontiers in Genetics, 2022)
Sweet sorghum (Sorghum dochna) is a high-quality bio-energy crop that also serves as food for humans and animals. However, there is little information on the genomic characteristics of S. dochna. In this study, we presented a high-quality assembly of S. dochna with PacBio long reads, Illumina short reads, high-throughput chromosome capture technology (Hi-C) sequencing data, gene annotation, and a comparative genome analysis. The results showed that the genome of S. dochna was assembled to 777 Mb with a contig N50 of 553.47 kb and a scaffold N50 of 727.11 kb. In addition, the gene annotation predicted 37,971 genes and 39,937 transcripts in the genome of S. dochna. A Venn analysis revealed a set of 7,988 common gene annotations by integrating five databases. A Cafe software analysis showed that 191 gene families were significantly expanded, while 3,794 were significantly contracted in S. dochna. A GO enrichment analysis showed that the expanded gene families were primarily clustered in the metabolic process, DNA reconstruction, and DNA binding among others. The high-quality genome map constructed in this study provides a biological basis for the future analysis of the biological characteristics of S. dochna, which is crucial for its breeding.